Chemistry made clear. - Gallagher, R.; Ingram, P. (Tokyo : Singapore : Oxford university press, 1998)
Chemistry Made Clear is widely used as a core GCSE Chemistry text, or as the Chemistry component of a balanced science course. Students will be able to find things out quickly and easily among the simplified explanations.
include index.
Keywords: Chemistry